Household Purposes in A Single Touch Via Bluetooth Using Smartphones - Bhavani Rohit; Rengamani J (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Technology emerges in our environment day by day. But, still, we lag in keep on using multiple remotes for every device in our homes. Once Bluetooth came up it changes. People started using mobile phones connected to their devices to hear songs wireless and change channels using a mobile phone. A further implementation is kept on moving with multiple remotes for their usage. So, we had an idea that all our household devices may be controlled on our mobile phones via Bluetooth which is cheaper even for urban peoples. Now, all home devices with remote are IR based which doesn't work on sunlight, fluorescent bulbs due to interference. Switch over Bluetooth control reduces remotes in a sense called plastics. Mobile applications are evolved user-friendly to all the people on the day to day lives. Merge those applications to the household devices to control all household devices operated via remote such as TV, DVD, Home theatres, AC, even Table fan etc., Instead of removing IR's just interface Bluetooth chip on those household devices to control every remote device by using your smartphone. Why I am moving to Bluetooth instead of Wi-Fi. Bluetooth is cheaper, advanced to control devices in the range of 50 meters. But IR is useful to 10 meters, and once you block the signal, it will not work.